High surface area polymer films by co-crystallization with low-molecular-mass guest molecules. (15th June 2022) - Nagendra, Baku; Daniel, Christophe; Rizzo, Paola; Guerra, Gaetano; Baldino, Lucia; Reverchon, Ernesto
Graphical abstract: Highlights: A general method to achieve high surface area (SA = 45–620 m 2 g −1 ) films for polymers exhibiting co-crystalline phases. Application of this preparation method to industrially relevant thermoplastic polymers: PLLA, sPS, and PPO. Fast guest-induced crystallization and fast guest extraction are required for the achievement of high SA polymer films. High SA films when exhibit nanoporous-crystalline (NC) phases show fast and high pollutant uptakes even at low activities. Kinetics of pollutant uptakes increase by two or three orders of magnitude, going from amorphous to high SA and NC film. Abstract: A general method to achieve high surface area (SA) films (SA in the range 45–620 m 2 /g), based on polymer co-crystallization with low-molecular-mass guests, is presented. The method requires fast guest-induced co-crystallization of amorphous polymer films, reaching high guest equilibrium contents (typically in the range 65–90 wt%), followed by fast guest removal from guest-reach co-crystalline films. This method is effective not only for polymers that by guest removal can lead to nanoporous-crystalline phases (like poly(2, 6-dimethyl-1, 4-phenylene)oxide, PPO and syndiotactic polystyrene, sPS) but also for polymers that by guest removal lead to usual dense crystalline phases (like polylactic acid, PLLA). These high SA films show guest uptakes at low activities which are high or negligible if the films exhibit nanoporous-crystalline (as for PPO and sPS) or dense phases (as for PLLA), respectively. Kinetic studies show that guest diffusivity can be increased by two or three orders of magnitude, going from amorphous to high SA NC films.